DRD2 Promoter Methylation and Measures of Alcohol Reward: Functional Activation of Reward Circuits and Clinical Severity - Bidwell, L. Cinnamon (Addict Biol, 2018)
Studies have identified strong associations between D2 receptor binding potential and neural responses to rewarding stimuli and substance use. Thus, D2 receptor perturbations are central to theoretical models of the pathophysiology of substance dependence, and epigenetic changes may represent one of the fundamental molecular mechanisms impacting the effect of alcohol exposure on the brain. We hypothesized that epigenetic alterations in the promoter region of the dopamine D2 receptor (DRD2) gene would be associated with cue-elicited activation of neural reward regions, as well as severity of alcohol use behavior. The current study leveraged functional neuroimaging (fMRI) during an alcohol reward paradigm (n=383) to test associations among DRD2 promoter methylation in peripheral tissue, signal change in the striatum during the presentation of alcohol cues, and severity of alcohol use disorder (AUD). Controlling for age, DRD2 promoter methylation was positively associated with responses to alcohol cues in the right accumbens (partial r=0.144, p=0.005), left putamen (partial r=0.133, p=0.009), right putamen (partial r=0.106, p=0.039), left caudate (partial r=0.117, p= 0.022), and right caudate (partial r=0.133, p=0.009), suggesting that DRD2 methylation was positively associated with robust activation in the striatum in response to reward cues. DRD2 methylation was also positively associated with clinical metrics of AUD severity. Specifically, controlling for age, DRD2 methylation was associated with AUDIT total (partial r=0.140, p=0.002); ICS total (partial r=0.097, p=0.044) and ADS total (partial r=0.152, p=0.001). Thus, DRD2 methylation may be a critical mechanism linking D2 receptors with functional striatal brain changes and clinical severity among alcohol users.